Relapsing Remitting Multiple Sclerosis in X-Linked Charcot-Marie-Tooth Disease with Central Nervous System Involvement - Koutsis, Georgios (Case Rep Neurol Med, 2015)
We report a patient with relapsing remitting multiple sclerosis (MS) and X-linked Charcot-Marie-Tooth disease (CMTX), carrying a GJB1 mutation affecting connexin-32 (c.191G>A, p. Cys64Tyr) which was recently reported by our group. This is the third case report of a patient with CMTX developing MS, but it is unique in the fact that other family members carrying the same mutation were found to have asymptomatic central nervous system (CNS) involvement (diffuse white matter hyperintensity on brain MRI and extensor plantars). Although this may be a chance association, the increasing number of cases with CMTX and MS, especially with mutations involving the CNS, may imply some causative effect and provide insights into MS pathogenesis.